Sperm nuclear protamines: A checkpoint to control sperm chromatin quality. (23rd May 2018) - Steger, Klaus; Balhorn, Rod
Abstract: Protamines are nuclear proteins which are specifically expressed in haploid male germ cells. Their replacement of histones and binding to DNA is followed by chromatin hypercondensation that protects DNA from negative influences by environmental factors. Mammalian sperm contain two types of protamines: PRM1 and PRM2. While the proportion of the two protamines is highly variable between different species, abnormal ratios within a species are known to be associated with male subfertility. Therefore, it is more than likely that correct protamine expression represents a kind of chromatin checkpoint during sperm development rendering protamines as suitable biomarkers for the estimation of sperm quality. This review presents an overview of our current knowledge on protamines comparing gene and protein structures between different mammalian species with particular consideration given to man, mouse and stallion. At last, recent insights into the possible role of inherited sperm histones for early embryo development are provided.